THE IMPORTANCE OF MATHEMATICS IN GENERAL SECONDARY EDUCATION - Toshboyeva Feruza Atamjanovna (Journals Park Publishing, 2023)
Mathematics is often perceived as a challenging subject, provoking a range of emotions from enthusiasm to anxiety among students. However, its significance in general secondary education cannot be overstated. Beyond being a subject to pass exams, mathematics equips students with critical thinking skills, problem-solving abilities, and a foundation for various careers. Mathematics is more than just numbers and equations; it is a tool that enhances cognitive abilities. The process of learning and applying mathematical concepts stimulates the brain, fostering logical reasoning, analytical thinking, and strategic planning.
Keywords: cognitive development, problem-solving skills, real-world applications, preparation for higher, education, technological literacy, enhancement of analytical, thinking, global competitiveness, critical thinking, logical reasoning, transferable skills.